2015
DOI: 10.22495/rgcv5i1art8
|View full text |Cite
|
Sign up to set email alerts
|

Capital structure and profitability. A case of JSE Listed Companies

Abstract: The research aims to find out the relationship between capital structure and profitability focusing on firms listed on the Johannesburg stock exchange in South Africa. Past research on this topic excluded the Johannesburg Stock Exchange listed firms. The research results will be useful to the business people in South Africa because it will be more in line with the South African economic status and thus relevant. From the graphs and tables of the companies analyzed, it appears there is no relationship between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The results showed that capital structure had positive impact on the financial performance of companies. Mashavave and Tsaurai (2015) analyzed the impact of financial structure on performance measures. The sample was composed of companies listed on the Johannesburg Stock Exchange in South Africa.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that capital structure had positive impact on the financial performance of companies. Mashavave and Tsaurai (2015) analyzed the impact of financial structure on performance measures. The sample was composed of companies listed on the Johannesburg Stock Exchange in South Africa.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, the assumptions of the theory take into account the phenomenon of financial distress that result from too much borrowing. Moreover, its assumption of optimal capital structure (leverage) has been the focal point of the finance literature for the past several decades due to contradicting results obtained from various empirical studies after testing the theory [4]. Therefore, this study was guided by the Traditional Trade-off theory.…”
Section: Introductionmentioning
confidence: 99%